Pengembangan Kurikulum Pendidikan Tinggi Berbasis KKNI SN-Dikti dan Kurikulum Merdeka dan OBE (Outcome Based Education) - Agus Pahrudin; Listiyani Siti Romlah; Murtando Murtando (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study aims to thoroughly investigate the factors that influence the integration of the Indonesian National Qualification Framework Curriculum (KKNI) SN-Dikti and the Merdeka Belajar Curriculum through a results-based education (OBE) approach, as well as providing concrete suggestions for improving the quality and relevance of learning at University. The research method uses a literature review methodology, which involves searching, analyzing and synthesizing relevant previous research. The results demonstrate the beneficial effects of combining the OBE approach with the KKNI SN-Dikti and Merdeka curricula on student learning in higher education. There is a significant increase in learning outcomes, including increasing knowledge relevant to the world of work and improving student soft skills. Project-based learning methods, active student participation, and flexible curricula were important components supporting this integration. Based on these findings, several suggestions for further research are proposed to deepen understanding of the integration of the KKNI SN-Dikti and Merdeka curriculum with the OBE approach and its social and ethical implications. Further research in this area is essential to develop higher education curricula aligned with contemporary demands and societal needs.